Budaya Patriarki Dalam Gadis Kretek: Analisis Semiotika Roland Barthes - Irmawati, Irmawati; Ayuni, Risa Dwi; Puspita, Amelia (Universitas Medan Area, 2025)
The purpose of this study is to examine how patriarchy culture is represented in the film Gadis Kretek. The research approach used by the researcher is descriptive qualitative with content analysis, utilizing both primary and secondary data sources. The data sources are analyzed using Roland Barthes's semiotic analysis, aiming to uncover the meanings contained in the film through three stages: denotation, connotation, and myth. The results of the research show that patriarchy culture in Gadis Kretek can be represented through 15 scenes, divided into four points: the limited gender roles, restrictions in self-expression, control over the lives of women and children, as well as oppression and discrimination against women. It is also concluded that denotative, connotative, and mythic meanings work together in the film to create a strong narrative that can be easily understood.